Costimulation blockade and Tregs in solid organ transplantation - Muckenhuber, Moritz; Wekerle, Thomas; Schwarz, Christoph (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) play a critical role in maintaining self-tolerance and in containing allo-immune responses in the context of transplantation. Recent advances yielded the approval of the first pharmaceutical costimulation blockers (abatacept and belatacept), with more of them in the pipeline. These costimulation blockers inhibit effector cells with high clinical efficacy to control disease activity, but might inadvertently also affect Tregs. Treg homeostasis is controlled by a complex network of costimulatory and coinhibitory signals, including CD28, the main target of abatacept/belatacept, and CTLA4, PD-1 and ICOS. This review shall give an overview on what effects the therapeutic manipulation of costimulation has on Treg function in transplantation.